The importance of scientific research activity in formation of teachers of higher education institutions - Radić Vlado (Trendovi u Poslovanju)
Scientific research at faculties (higher schools) can not and should not be understood as an obligation in order to fulfill certain conditions for promotion. Although the time periods of the selection of teaching titles are determined by law, young teachers are expected to show more enthusiasm, diligence, initiative, and extraordinary dedication to the job they will deal with. The teaching process requires continuous improvement, even in a small segment of total knowledge, but this knowledge is acquired in different ways. The time in which we live is increasingly emphasized by learning organizations, and they are based on new knowledge. The dispersion of this knowledge, even to students, represents an important segment in the formation of teachers. It is therefore necessary to encourage young teachers to actively engage in scientific research work in an area they feel they are capable of handling and progressing. The paper outlines the basic criteria that point to the importance of scientific research in higher education institutions, with a focus on the process of formation, management and development of future teachers.